Peningkatan Kompetensi Guru dalam Pembelajaran Interaktif melalui Pemanfaatan Nearpod: Sebuah Kegiatan Pengabdian kepada Masyarakat - Rispah Purba; Alim Mutaqin; Tiffany Shahnaz Rusli; Daud Kaigere; Firda Wati; Sara Cesilia (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement program aimed to improve teachers competence in designing and implementing interactive digital learning through the use of Nearpod, while also providing basic knowledge for the surrounding community on managing small businesses with digital approaches. The implementation method was carried out in several stages, including needs analysis, training sessions, development of interactive modules, classroom implementation, and reflective evaluation. The results revealed a significant improvement in teachers knowledge and skills, as indicated by the increase in pre-test and post-test scores and the successful creation of five interactive learning modules that were directly applied in classrooms. Students demonstrated greater enthusiasm and participation during the learning process, while the community gained useful insights to support their economic activities. The conclusion drawn from this program is that the use of Neaarpod can effectively enhance the quality of learning, foster students motivation, and strengthen teachers roles as creative facilitators in the classroom, while also contributing positively to the surrounding community.